Electrode Reactions of Copper Species in a Bis(fluorosulfonyl)amide Ionic Liquid - Nobuyuki SERIZAWA; Takumi HISADA; Yasushi KATAYAMA (Electrochemistry, 2024)
The electrode reactions of copper species were investigated in an amide-type ionic liquid, 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl) amide (BMPFSA). The anodic current assignable to the dissolution of Cu to form monovalent Cu(I) complex was observed at −0.42 V vs. Ag|Ag(I). A pair of anodic and cathodic current peaks attributable to Cu(II)/Cu(I) was observed at 0.5 V, suggesting that a 4 V class redox flow battery combined with a Li metal anode is expected using the redox reaction of Cu(II)/Cu(I) in BMPFSA as the cathode reaction. The electrodeposition of Cu and the quasi-reversible redox reaction of Cu(II)/Cu(I) were affected by the electrode materials.